Preparation method and application of p element doped modified fe-nc catalyst

CN123033989APending Publication Date: 2026-11-03KUNMING UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610867271.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing Fe-NC catalysts are not stable enough under harsh electrochemical conditions, making it difficult to achieve simultaneous and controllable preparation and stable coexistence of FeP and Fe2P phases. The preparation methods are complex and not conducive to large-scale production. Existing P-doping technologies have safety and demanding conditions.

Method used

Phytic acid, a phosphorus-containing ligand, forms a strong coordination relationship with iron ions. The Fe-P chemical structure is constructed in situ through a two-stage pyrolysis process to form a FeP/Fe2P homologous heterojunction, thus preparing a P-doped modified Fe-NC catalyst.

Benefits of technology

It significantly improves the intrinsic activity, long-term stability and resistance to methanol poisoning of the catalyst in oxygen reduction and oxygen evolution reactions, outperforming commercial Pt/C and RuO2 catalysts, and is applied to high-performance zinc-air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033989A_ABST
    Figure CN123033989A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a P element doped modified Fe-NC catalyst. 3+ The method utilizes the strong coordination of a phosphoric acid group in phytic acid and Fe to form a coordination precursor, and prepares an FeP / Fe2P-NC catalyst through two-stage pyrolysis carbonization. The catalyst contains FeP and Fe2P nanoparticles loaded on an N and P co-doped porous carbon carrier, retains a high specific surface area morphology, and optimizes the electronic structure of Fe sites through electronic regulation of P atoms. The catalyst has an ORR half-wave potential of 0.861 V in 0.1 M KOH, which is superior to that of a commercial Pt / C; the OER overpotential is only 375 mV (50 mA cm ‑2 ) in 1 M KOH, which is superior to that of a commercial RuO2; when applied to a zinc-air battery, the open-circuit voltage is 1.43 V, the peak power density is 161 mW cm ‑2 , and the cycle stability is 200,000 s, which is superior to that of a commercial Pt / C+RuO2 system. The application has a simple process, excellent stability and a wide industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical technology, specifically to a method for preparing and applying a phosphorus-doped modified Fe-NC catalyst. Background Technology

[0002] With the growing global demand for clean energy and efficient energy conversion technologies, fuel cells and metal-air batteries (such as zinc-air batteries) have attracted significant attention due to their high energy density and zero-emission characteristics. However, the cathode kinetics of these devices, namely the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), involve complex multi-electron transfers, resulting in high reaction energy barriers and slow kinetics, which severely limit the overall performance of the battery. Currently, commercial catalysts mainly rely on precious metal materials such as platinum (Pt), ruthenium (Ru), and iridium (Ir), but their high cost, limited natural reserves, and instability during long-term operation (such as dissolution, agglomeration, and poisoning) greatly hinder the large-scale commercial application of related technologies.

[0003] To replace noble metal catalysts, researchers have developed various non-noble metal-based materials. Among them, transition metal-nitrogen-carbon (MNC, M = Fe, Co, Ni, etc.) materials, especially iron-based (Fe-NC) catalysts, have shown ORR initiation activity and half-wave potential comparable to Pt / C in alkaline media, and are considered a very promising alternative system. Their activity mainly originates from atomically dispersed Fe-Nx sites or supported metal nanoparticles. Nevertheless, Fe-NC catalysts, especially the most active Fe-N4 sites, still face significant challenges in terms of stability under harsh electrochemical conditions (such as high potential, acidic / alkaline media, and long-term cycling). The Fe centers are prone to oxidation, dissolution, or Fenton reactions with reaction intermediates (such as H₂O₂), leading to degradation, loss of active sites, and performance degradation.

[0004] Heteroatom doping is an effective means of modulating the electronic structure of carbon-based materials and improving their catalytic activity and stability. Among many doping elements, phosphorus (P) atoms, due to their low electronegativity and large atomic radius, can effectively regulate the local charge distribution and electronic structure of the carbon substrate, thereby improving the adsorption / desorption behavior of reaction intermediates on the catalyst surface and optimizing reaction kinetics. More importantly, P can form a strong Fe-P interaction with the transition metal Fe. Compared to Fe-N bonds, Fe-P bonds generally have higher chemical stability, which is beneficial for constructing corrosion-resistant and oxidation-resistant active centers.

[0005] In recent years, heterostructure design has been widely used to improve the performance of electrocatalytic materials. Among them, homologous heterojunctions composed of different compositions or different crystal phases in the same elemental system have advantages such as good component compatibility, tight interfacial bonding, and significant electronic coupling effects. However, existing technologies still face significant challenges in preparing P-doped Fe-based catalysts, especially homologous heterojunction catalysts. First, existing methods usually require multi-step high-temperature phosphating treatments or rely on phosphorus sources such as hypophosphite, which have certain toxicity and hazards, resulting in complex processes, harsh conditions, poor safety, and difficulties in large-scale preparation. Second, FeP and Fe2P are iron phosphide phases with different phosphorus contents, and their formation process is highly sensitive to conditions such as temperature, atmosphere, phosphorus source release rate, and precursor composition. In actual synthesis, phenomena such as single phase formation, phase imbalance, particle agglomeration, or overphosphating are prone to occur, making it difficult to achieve the simultaneous and controllable preparation and stable coexistence of the FeP and Fe2P phases. Summary of the Invention

[0006] The purpose of this invention is to provide a simple and mild method for preparing a phosphorus-doped modified Fe-NC catalyst and its application. This method utilizes the strong coordination between a phosphorus-containing ligand and iron ions to directionally construct a stable iron-phosphorus (Fe-P) chemical structure in the catalyst. Furthermore, a two-stage pyrolysis process is used to form a homo-heterojunction in situ, thereby significantly improving the catalyst's intrinsic activity, long-term stability, and resistance to methanol poisoning in the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). This catalyst can then be applied to high-performance zinc-air batteries to replace expensive noble metal catalysts.

[0007] In a first aspect, the present invention provides a method for preparing a P-doped modified Fe-NC catalyst, comprising the following steps: (1) Anhydrous ferric chloride, ultra-high conductivity carbon black BP2000 and dicyandiamide were ultrasonically dispersed in deionized water and then vigorously stirred in an oil bath until a completely homogeneous mixture was formed; phytic acid solution was slowly added dropwise to the above mixture, and the mixture was heated and stirred in an oil bath until the water evaporated completely. The black solid mixture was collected, dried and ground to obtain the black solid precursor. (2) The black solid precursor obtained in step (1) is placed in a tube furnace and subjected to two-stage pyrolysis under nitrogen atmosphere protection. Then it is naturally cooled to room temperature to obtain FeP / Fe2P-NC catalyst; that is, P element doped modified Fe-NC catalyst.

[0008] Furthermore, in step (1), the proportions of anhydrous ferric chloride, ultra-high conductivity carbon black BP2000, dicyandiamide, deionized water, and phytic acid solution are as follows: 0.3mmol:80-120mg:20-27mmol:25-40mL:85-105μL; The phytic acid solution has a mass concentration of 70%.

[0009] Furthermore, in step (1), the ultrasonic treatment time is 1-4 min; the oil bath temperature is 55-65℃.

[0010] Furthermore, in step (2), the two-stage pyrolysis includes a pre-carbonization stage and a high-temperature carbonization stage, with the following conditions: the pre-carbonization stage temperature is 530-560°C, the heating rate is 2-3°C / min, and the holding time is 1.5-2.5h; the high-temperature carbonization stage temperature is 770-820°C, the heating rate is 3-5°C / min, and the holding time is 1.5-2.5h.

[0011] Secondly, the present invention provides an application of the P-doped modified Fe-NC catalyst prepared by the above method, in which the catalyst is used as an electrochemical catalyst in oxygen reduction reaction and oxygen evolution reaction under alkaline conditions, as well as as a cathode catalyst in zinc-air batteries.

[0012] The beneficial effects of this invention are as follows: (1) In this invention, phytic acid is used as a phosphorus-containing ligand, which utilizes the multiple phosphate groups in its molecule to react with Fe. 3+ The coordination and chelation between them form a well-dispersed Fe-P coordination precursor, which is beneficial for limiting the migration and aggregation of Fe species during subsequent pyrolysis, and promotes the in-situ formation and stable coexistence of FeP and Fe2P phases, thereby constructing a P-doped Fe-NC catalyst with Fe-P active structure.

[0013] (2) This invention employs a two-stage pyrolysis carbonization process. The low-temperature pre-carbonization stage facilitates the initial formation of the carbon skeleton in the precursor and the fixation of the Fe-P coordination structure. The high-temperature carbonization stage further promotes the formation of the iron phosphide phase, the construction of the FeP / Fe2P homologous heterostructure interface, and the graphitization of the carbon support. By constructing the material through two-stage pyrolysis, the electronic structure of the active site and the charge transfer efficiency of the catalyst can be optimized, thereby improving its ORR / OER bifunctional electrocatalytic performance.

[0014] (3) The catalyst prepared in this invention exhibits excellent ORR / OER bifunctional catalytic performance, with an ORR half-wave potential of 0.844-0.861V, which is superior to commercial Pt / C; the OER overpotential (50mA cm⁻¹) is also superior. -2 With a voltage of only 375-412mV, it outperforms commercial RuO4. 2 It is used in zinc-air batteries with an open-circuit voltage of 1.43V and a peak power density of 161mW / cm³. -2 Specific capacity 791mAh g -1 The cycle stability reaches 200,000s, which is significantly better than the commercial Pt / C+RuO2 system. Attached Figure Description

[0015] Figure 1 The X-ray diffraction (XRD) pattern of the sample from Example 1 is shown below. Figure 2 The image shown is a field emission scanning electron microscope (FE-SEM) image of the sample from Example 1. Figure 3 Transmission electron microscopy (TEM) image of sample 1 in Example 1 ( Figure 3 ac represents TEM images at different scales. Figure 3 d is a high-resolution TEM (HR-TEM) image); Figure 4 High-resolution XPS spectra of Fe 2p, N 1s, and P 2p from the sample of Example 1 ( Figure 4 a represents the Fe 2p spectrum. Figure 4 b is the N 1s spectrum, Figure 4 c represents the P 2p spectrum. Figure 5 The oxygen reduction reaction (ORR) polarization curves for the sample of Example 1 and Pt / C are shown. Figure 6 Example 1: Oxygen evolution reaction (OER) polarization curves of the sample and RuO2; Figure 7 The open-circuit voltage, discharge polarization curves, power density, specific capacity, and charge-discharge cycle stability test results of the zinc-air battery assembled with the sample from Example 1 and Pt / C-RuO2 are shown in the figure. Figure 7 diagram a shows the open-circuit voltage. Figure 7 b shows the discharge polarization curve and power density plot. Figure 7 c is the specific capacity chart. Figure 7 d represents the charge-discharge cycle stability diagram. Detailed Implementation

[0016] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention, but the scope of protection of the present invention is not limited thereto.

[0017] Unless otherwise specified, all raw materials used in the embodiments of the present invention are commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meaning as commonly understood by those skilled in the art.

[0018] Example 1: (1) 0.3 mmol anhydrous ferric chloride, 100 mg BP2000 and 24 mmol dicyandiamide were added to 30 mL of deionized water and sonicated for 2 min; the mixture was placed in a 60°C oil bath and stirred vigorously until completely homogeneous; 100 μL phytic acid solution (70 wt%) was slowly added to the above mixture, and the mixture was heated and stirred in a 60°C oil bath until the water evaporated. The black solid mixture was collected, dried and ground to obtain a black solid precursor. (2) The black solid precursor obtained in step (1) was placed in a tube furnace and subjected to two-stage pyrolysis carbonization under nitrogen gas flow protection: first, the temperature was raised to 550°C at a rate of 2.5°C / min and held for 2 hours; then the temperature was raised to 800°C at a rate of 4°C / min and held for 2 hours, and then naturally cooled to room temperature to obtain the FeP / Fe2P-NC catalyst, which was recorded as the sample of Example 1.

[0019] The sample of Example 1 obtained in step (2) was subjected to X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS) tests, respectively. Figure 1 , Figure 2 , Figure 3 , Figure 4 .

[0020] Depend on Figure 1 It can be seen that the XRD spectrum of the sample in Example 1 ( Figure 1 The sample exhibited characteristic diffraction peaks for FeP and Fe2P, which highly matched those of standard cards PDF#89-2746 and PDF#89-3680, confirming the presence of both FeP and Fe2P phases in the sample of Example 1. Furthermore, a broad peak was observed in the diffraction angle range of 20-26°, indicating that the material may contain a certain amount of amorphous carbon or low-graphitized carbon, coexisting with the FeP / Fe2P phases to form a composite structure. Figure 2 It can be seen that the sample of Example 1 retained a large number of small-sized carbon nanoparticles, maintaining the morphology of the BP2000 porous carbon support. At the same time, some large-sized blocky substances (white dashed boxes) were observed, which may be Fe phosphide particles. Figure 3 a- Figure 3 c indicates that the TEM image of the sample in Example 1 shows the presence of metal nanoparticles on the carbon support, while the HR-TEM image ( Figure 3 d) The lattice spacings of the nanoparticles are 0.266 nm and 0.224 nm, respectively, corresponding to the (211) crystal plane of FeP and the (111) crystal plane of Fe2P, further confirming the existence of a two-phase structure of FeP and Fe2P, and the presence of a clear and continuous interface, indicating the formation of a heterojunction. XPS characterization of the sample from Example 1 was performed. Figure 4The results showed that Fe-P bound state characteristic peaks existed in the Fe 2p spectrum, and Fe could also be observed. 2+ and Fe 3+ The peaks and satellite peaks indicate that iron in the sample exists in multiple valence states. Figure 4 The presence of graphitic nitrogen, pyrrolic nitrogen, Fe-Nx, and pyridinic nitrogen peaks in the b N 1s spectrum indicates that nitrogen in the sample exists in multiple chemical environments. Figure 4 The cP 2p spectrum showed peaks for PC, PO, and Fe-P binding states, indicating that phosphorus exists in multiple chemical states in the sample. The XPS results above demonstrated the chemical states and relative distribution of Fe, N, and P in the sample of Example 1. In summary, a P-doped modified Fe-NC catalyst was successfully synthesized. The reason for this structure is that the first-stage low-temperature pyrolysis allows dicyandiamide to undergo thermal condensation and form a nitrogen-rich carbon intermediate framework, while simultaneously promoting the further solidification and rearrangement of the phytic acid-crosslinked metal composite precursor, thus completing pre-carbonization and creating conditions for subsequent high-temperature phosphating. The second-stage high-temperature pyrolysis causes Fe to undergo a reduction-phosphating reaction under nitrogen protection and a carbon environment. Fe2P is more easily formed under lower temperatures and lower phosphorus atom fractions, while longer reaction times and faster heating tend to favor the formation of the higher phosphorus content FeP phase. Therefore, some Fe first forms the iron-rich Fe2P phase, while in regions with higher local phosphorus activity and more complete reaction, Fe2P can further transform into FeP, ultimately forming an in-situ FeP / Fe2P homojunction.

[0021] The sample of Example 1 obtained in step (2) was used for electrochemical performance testing. The testing method is as follows, and the test results are shown in [see attached image]. Figure 5 , Figure 6 and Figure 7 And Table 1: ORR performance testing: A three-electrode system was used on a CHI 760E electrochemical workstation to test the catalyst film (loading 0.6 mg cm⁻¹). -2 A glassy carbon rotating disk electrode (RDE, 5 mm in diameter) was used as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The test was conducted in an O2-saturated 0.1 M KOH electrolyte. The test results are shown below. Figure 5 .

[0022] Depend on Figure 5As shown in Table 1, the ORR onset potentials of the samples in Examples 1-3 were 0.968V, 0.943V, and 0.950V, respectively, and the half-wave potentials were 0.861V, 0.844V, and 0.847V, respectively. These values ​​were superior to those of Comparative Example 1 (0.937V, 0.822V), Comparative Example 2 (0.919V, 0.796V), and Comparative Example 3 (0.910V, 0.781V), and were close to those of commercial Pt / C (0.967V, 0.843V). Table 1 also shows that the Tafel slopes of the samples in Examples 1-3 were only 84.8, 99.4, and 97.6 mV dec, respectively. -1 The values ​​were all lower than those of comparative samples 1-3, indicating that it had the fastest catalytic reaction rate.

[0023] OER performance test: In 1M KOH electrolyte, the catalyst was supported on nickel foam (loading amount 1.0 mg cm⁻¹). -2 The electrode was a platinum sheet as the counter electrode, and Ag / AgCl (saturated KCl) as the reference electrode. Electrochemical impedance spectroscopy (Rct) was compensated at 80%. Test results are shown below. Figure 6 See Table 1.

[0024] Depend on Figure 6 As shown in Table 1, at 50 mA cm -2 At the given current density, the overpotential of the sample in Example 1 was 375 mV, significantly lower than that of RuO2 (424 mV). As shown in Table 1, the Rct of the sample in Example 1 was 0.73 Ω, significantly lower than that of the other comparative example 3, indicating that it has the highest relative charge transfer efficiency.

[0025] Zinc-air battery test: A mixed solution of 6.0M KOH and 0.2M ZnAc2 was used as the electrolyte, a 0.2mm thick zinc sheet was used as the negative electrode, and a catalyst (1.0mg cm⁻¹) was supported. -2 A zinc-air battery was assembled using a carbon paper-nickel foam composite electrode as the air cathode and tested. The test results are shown below. Figure 7 .

[0026] Depend on Figure 7 As can be seen from this, the open-circuit voltage of the sample in Example 1 used in a zinc-air battery is 1.43V, which is superior to that of commercial Pt / C+RuO2 (1.40V). From Figure 7 As can be seen from b, the peak power density of the sample in Example 1 used in a zinc-air battery is 161 mW / cm². -2 Compared to commercial Pt / C+RuO2 (120mW cm⁻¹) -2 (This represents an increase of 34.2%.) Figure 7 c indicates that the sample from Example 1 has a specific capacity of 791 mAh g for use in a zinc-air battery. -1 Surpassing commercial Pt / C+RuO2 (770mAh g)-1 ).Depend on Figure 7 As can be seen from d, the sample of Example 1 remained stable after 200,000 s of charge-discharge cycles in a zinc-air battery, while the commercial Pt / C+RuO2 failed after 125,000 s.

[0027] In summary, based on structural characterization and electrochemical testing results, the excellent ORR / OER electrocatalytic performance of the sample in Example 1 is related to its FeP / Fe2P-NC composite structure. The formation of the FeP / Fe2P homologous heterostructure interface is beneficial for regulating the electronic environment of Fe-related active sites and improving the adsorption / desorption behavior of oxygen-containing intermediates during the oxygen reaction. The N and P co-doped carbon framework and porous carbon nanoparticle morphology are beneficial for improving conductivity, increasing the exposure of active sites, and promoting electrolyte contact. Therefore, the sample in Example 1 exhibits good bifunctional electrocatalytic performance in ORR and OER tests.

[0028] Example 2: (1) 0.3 mmol anhydrous ferric chloride, 80 mg BP2000 and 20 mmol dicyandiamide were added to 25 mL of deionized water and sonicated for 1 min; the mixed solution was placed in a 55°C oil bath and stirred vigorously until completely homogeneous; 85 μL phytic acid solution (70%) was slowly added dropwise to the above mixture, and the mixture was heated and stirred in a 55°C oil bath until the water evaporated. The black solid mixture was collected, dried and ground to obtain a black solid precursor. (2) The black solid precursor obtained in step (1) was placed in a tube furnace and subjected to two-stage pyrolysis carbonization under nitrogen gas flow protection: first, the temperature was raised to 530°C at a rate of 3°C / min and held for 2.5h; then the temperature was raised to 770°C at a rate of 5°C / min and held for 2.5h, and then naturally cooled to room temperature to obtain the FeP / Fe2P-NC catalyst, which was recorded as the sample of Example 2.

[0029] The XRD test was performed on the sample of Example 2 obtained in step (2). The test results are presented in the form of phase composition. The test structure is shown in Table 1.

[0030] As shown in Table 1, the sample of Example 2 consists of two phases, FeP and Fe2P, which is consistent with Example 1.

[0031] The sample of Example 2 obtained in step (2) was used for electrochemical performance testing. The testing method was the same as above, and the test results are shown in Table 1: As shown in Table 1, the ORR initiation potential in Example 2 is 0.943V, the half-wave potential is 0.844V, and the Tafel slope is 99.4mV dec. -1 The overpotential of OER is 412mV (50mA cm). -2The Rct value is 0.95Ω, indicating that it also has excellent ORR and OER performance as well as relatively high charge transport efficiency.

[0032] Example 3: (1) 0.3 mmol of anhydrous ferric chloride, 120 mg of BP2000 and 27 mmol of dicyandiamide were added to 40 mL of deionized water and sonicated for 4 min. The mixture was placed in a 65°C oil bath and stirred vigorously until completely homogeneous. 105 μL of phytic acid solution (70%) was slowly added to the mixture. The mixture was heated and stirred in a 65°C oil bath until the water evaporated. The black solid mixture was collected, dried and ground to obtain a black solid precursor. (2) The black solid precursor obtained in step (1) was placed in a tube furnace and subjected to two-stage pyrolysis carbonization under nitrogen gas flow protection: first, the temperature was raised to 560°C at a rate of 2°C / min and held for 1.5h; then the temperature was raised to 820°C at a rate of 3°C / min and held for 1.5h, and then naturally cooled to room temperature to obtain the FeP / Fe2P-NC catalyst, which was recorded as the sample of Example 3.

[0033] The XRD test was performed on the sample of Example 3 obtained in step (2). The test results are presented in the form of phase composition. The test structure is shown in Table 1.

[0034] As shown in Table 1, the sample of Example 3 is composed of FeP and Fe2P phases, which is consistent with that of Example 1.

[0035] The sample of Example 3 obtained in step (2) was used for electrochemical performance testing. The testing method was the same as above, and the test results are shown in Table 1: As shown in Table 1, the ORR onset potential of the sample in Example 3 was 0.950V, the half-wave potential was 0.847V, and the Tafel slope was 97.6mV dec. -1 The overpotential of OER is 403mV (50mA cm). -2 Its Rct is 0.88Ω, indicating that it also has excellent ORR and OER performance as well as relatively high charge transport efficiency.

[0036] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that phytic acid is not added in step (1), while other steps remain unchanged. Fe-NC catalyst is prepared and is recorded as Comparative Example 1 sample.

[0037] The comparative example 1 sample obtained in step (2) was subjected to XRD test. The test results are presented in the form of phase composition. The test results are shown in Table 1.

[0038] As shown in Table 1, the Fe species in the Comparative Example 1 sample exist in the forms of elemental iron and FeN. 0.0324Unlike Fe3O4, phytic acid lacks characteristic peaks for FeP and Fe2P. This is because phytic acid, acting as a phosphorus source, forms a strong chelate complex with Fe ions through its six phosphate groups, pre-organizing the precursor at low temperatures to achieve uniform dispersion and confinement of Fe species. Subsequently, during high-temperature pyrolysis, the phosphate groups release active phosphorus species, promoting in-situ reduction-phosphating reactions of iron salts, thereby generating FeP and Fe2P phases. Simultaneously, these phases synergistically form an N, P co-doped carbon framework with the N source provided by dicyandiamide, effectively anchoring the phosphide particles. Without the introduction of phytic acid, the phosphating pathway is blocked, and Fe exists primarily in oxide, nitride, and metallic states.

[0039] The Comparative Example 1 sample obtained in step (2) was used for electrochemical performance testing. The testing method was the same as above, and the test results are shown in Table 1: The half-wave potential of Comparative Example 1 was 0.822V, and the onset potential was 0.937V, significantly lower than that of Examples 1-3, and its Tafel slope was 106.5mV dec. -1 The OER overpotential was significantly higher than that of the samples in Examples 1-3, indicating a relatively slow chemical reaction rate. The OER overpotential was 421 mV, and the Rct was 2.59 Ω, significantly higher than those of the samples in Examples 1-3, indicating weaker catalytic performance and a significantly reduced charge transport efficiency. This may be because Comparative Example 1 did not include phytic acid, lacking the coordination confinement of Fe species by the phosphate groups in phytic acid and the subsequent phosphating effect, thus making it difficult to form Fe-P binding structures and FeP / Fe2P homologous heterojunction interfaces. For the ORR process, the electronic environment of Fe-related active sites was not effectively regulated, which is detrimental to oxygen molecule adsorption activation and the adsorption / desorption balance of oxygen-containing intermediates. For the OER process, the lack of Fe-P active structures and the synergistic effect of heterojunction interfaces may be unfavorable for OH... - The oxygen-containing intermediates involved undergo gradual transformation, and their large charge transfer resistance also limits electron transport during the reaction. Therefore, the Comparative Example 1 sample exhibits lower ORR activity and poorer OER catalytic performance than the Sample of Example 1.

[0040] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that in step (2), a one-stage high-temperature pyrolysis carbonization is performed. The pyrolysis conditions are: heating to 800°C at a rate of 5°C / min and holding for 2 hours. Other steps remain unchanged. FeP-NC catalyst is prepared and is referred to as Comparative Example 2 sample.

[0041] The comparative sample 2 obtained in step (2) was subjected to XRD test. The test results are presented in the form of phase composition. The test results are shown in Table 1.

[0042] As shown in Table 1, the Comparative Example 2 sample consists only of the FeP phase. This is because the direct one-step high-temperature pyrolysis carbonization lacks the low-temperature pre-condensation and phosphating buffer stages. Under high-temperature conditions, active phosphorus species are rapidly released and fully react with Fe, and the kinetic path is more biased towards the complete phosphating path, thus preferentially forming the stable FeP phase with a higher phosphorus content.

[0043] The comparative sample 2 obtained in step (2) was used for electrochemical performance testing. The testing method was the same as above, and the test results are shown in Table 1.

[0044] As shown in Table 1, the half-wave potential of Comparative Example 2 was 0.796 V, and the onset potential was 0.919 V, significantly lower than that of Examples 1-3, while the Tafel slope was 111.3 mV dec. -1 The OER overpotential was 429 mV, and the Rct was 2.36 Ω, significantly higher than those of the samples in Examples 1-3. This may be because Comparative Example 2 used a one-stage high-temperature pyrolysis carbonization process, which failed to form a dual-phase structure with coexisting FeP and Fe2P and a homologous heterogeneous interface. The lack of synergistic regulation from the dual-phase interface in the single FeP phase makes it difficult to fully optimize the electronic environment of Fe-related active sites. For the ORR process, its regulatory effect on oxygen molecule adsorption activation and the adsorption / desorption process of oxygen-containing intermediates is relatively insufficient, thus exhibiting a lower onset potential, half-wave potential, and a higher Tafel slope. For the OER process, the lack of synergistic effect from the FeP / Fe2P heterogeneous interface is detrimental to OH... - The oxygen-containing intermediates involved undergo gradual transformation, while the relatively large charge transfer resistance indicates that the electron transport process is relatively limited. Therefore, the ORR and OER electrocatalytic performance of the Comparative Example 2 sample are both lower than those of the Example 1 sample, indicating that the FeP / Fe2P biphase structure formed by the two-stage pyrolysis and its interfacial synergistic effect play an important role in improving the bifunctional oxygen electrocatalytic performance.

[0045] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that in step (2), a one-stage low-temperature pyrolysis carbonization is performed. The pyrolysis conditions are: heating to 550°C at a rate of 2.5°C / min and holding for 2 hours. Other steps remain unchanged. Fe2P-NC catalyst is prepared and is referred to as Comparative Example 3 sample.

[0046] XRD tests were performed on the comparative example 3 sample obtained in step (2). The test results are presented in the form of phase composition. The test results are shown in Table 1.

[0047] As shown in Table 1, the sample of Comparative Example 3 consists only of the Fe2P phase. This is because the direct one-step low-temperature pyrolysis carbonization resulted in limited phosphorus-containing activity released from the decomposition of phytic acid. Fe initially reacted with readily available P sources, tending to form the iron-rich Fe2P phase. However, the lack of sustained thermal energy from the subsequent high-temperature stage prevented sufficient atomic diffusion, crystal phase reconstruction, and further phosphating, making it difficult for some Fe2P to transform into the other phosphide phase, FeP.

[0048] The comparative sample 3 obtained in step (2) was used for electrochemical performance testing. The testing method was the same as above, and the test results are shown in Table 1.

[0049] As shown in Table 1, the half-wave potential of Comparative Example 3 was 0.781 V, and the onset potential was 0.910 V, which were significantly lower than those of Examples 1-3. Furthermore, its Tafel slope was 118.2 mV dec. -1 The OER overpotential was 424 mV, and the Rct was 2.27 Ω, significantly higher than that of the samples in Examples 1-3. This may be because Comparative Example 3 used a one-stage low-temperature pyrolysis carbonization, which mainly formed a single Fe2P phase and failed to construct the FeP / Fe2P biphase structure and homologous heterostructure interface as in Example 1. Due to the lack of synergistic regulation by the biphase interface, the electronic environment of its Fe-related active sites is difficult to optimize sufficiently, which is not conducive to the adsorption and activation of oxygen molecules and the adsorption / desorption of oxygen-containing intermediates during the ORR process, nor is it conducive to the adsorption and desorption of OH during the OER process. - The oxygen-containing intermediates involved undergo continuous transformation. However, the relatively large charge transfer resistance indicates that the electron transport process is relatively limited. Therefore, the ORR and OER performance of Comparative Example 3 are both lower than those of Example 1, further demonstrating that the FeP / Fe2P biphase structure formed by the two-stage pyrolysis and the interfacial synergistic effect are beneficial to improving the bifunctional oxygen electrocatalytic performance.

[0050] Table 1 presents the XRD and electrocatalytic performance test results of Examples 1-3 and Comparative Examples 1-3. The XRD results are presented in the form of phase composition, and the electrocatalytic performance test results are presented as ORR onset potential (V), ORR half-wave potential (V), and ORR Tafel slope (mV dec). -1 OER overpotential (mV) and OER charge transfer resistance Rct (Ω) are presented in the form of OER overpotential (mV) and OER charge transfer resistance Rct (Ω).

[0051] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of protection of the present invention.

Claims

1. A method for preparing a phosphorus-doped modified Fe-NC catalyst, characterized in that, Includes the following steps: (1) Anhydrous ferric chloride, ultra-high conductivity carbon black BP2000 and dicyandiamide were ultrasonically dispersed in deionized water and then vigorously stirred in an oil bath until a completely homogeneous mixture was formed; phytic acid solution was slowly added dropwise to the above mixture, and the mixture was heated and stirred in an oil bath until the water evaporated completely. The black solid mixture was collected, dried and ground to obtain the black solid precursor. (2) The black solid precursor obtained in step (1) was placed in a tube furnace and subjected to two-stage pyrolysis under nitrogen atmosphere protection. Then it was naturally cooled to room temperature to obtain FeP / Fe2P-NC catalyst. This refers to the P-doped modified Fe-NC catalyst.

2. The preparation method of the P-doped modified Fe-NC catalyst according to claim 1, characterized in that, In step (1), the ratio of anhydrous ferric chloride, ultra-high conductivity carbon black BP2000, dicyandiamide, deionized water, and phytic acid solution is 0.3 mmol: 80-120 mg: 20-27 mmol: 25-40 mL: 85-105 μL; the mass concentration of the phytic acid solution is 70%.

3. The method for preparing the P-doped modified Fe-NC catalyst according to claim 1, characterized in that, In step (1), the ultrasonic treatment time is 1-4 min; the oil bath temperature is 55-65℃.

4. The preparation method of the P-doped modified Fe-NC catalyst according to claim 1, characterized in that, In step (2), the two-stage pyrolysis includes a pre-carbonization stage and a high-temperature carbonization stage, with the following conditions: the pre-carbonization stage temperature is 530-560°C, the heating rate is 2-3°C / min, and the holding time is 1.5-2.5h; the high-temperature carbonization stage temperature is 770-820°C, the heating rate is 3-5°C / min, and the holding time is 1.5-2.5h.

5. The application of a P-doped modified Fe-NC catalyst prepared by any one of the preparation methods described in claims 1-4, characterized in that, The catalyst can be used as an electrochemical catalyst in oxygen reduction and oxygen evolution reactions under alkaline conditions, or as a cathode catalyst in zinc-air batteries.